Usability Evaluation of Mobile-Based Application for Javanese Script Learning Media - Dewi, Ratih Kartika; Priandani, Nurizal Dwi; Brata, Komang Candra; Fanani, Lutfi (Faculty of Computer Science (FILKOM) Brawijaya University, 2018)
Indonesian people should actively preserve Indonesian culture. A way to preserve Indonesian culture can be done by using Javanese scripts as a local content subject at elementary to middle school level. In the conventional learning method, almost all teachers teach writing Javanese manuscript with conventional instructional media by using a white board. We proposed a mobile application that can help students to learn how to write Javanese script in attractive way by using their finger. Since this application still in prototype stage, further study and analysis of the usability of this application are necessary to validate the feasibility in real implementation. Usability testing using USE questionnaire had been conducted to find out if application of Javanese script writing can be accepted by users. We give 30 questions about usability to 5 respondents that are familiar with android application. The result show that, the proposed application is acceptable to users in term of Usefulness, ease of use, ease of learning and satisfaction.